Modified material and preparation method thereof, and polycaproic acid butylene terephthalate film
By activating the micron-scale calcium carbonate, melt extrusion with PBAT, and combining specific additives to prepare modified materials, the problem of difficult to take into account in the existing technology is solved, and high-performance and environmentally friendly film preparation is achieved.
Patent Information
- Application Number
- CN202510191819.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When using calcium carbonate to modify PBAT, it is difficult to improve the performance of PBAT and maintain its good biodecomposition rate in the prior art. The degradation rate of modified micron-scale calcium carbonate in the natural environment becomes slower, which poses environmental hazards.
By activating micron-scale calcium carbonate and silane coupling agent in a powder activation device, activated micron-scale calcium carbonate is formed, and melt extruded with PBAT through a twin-screw extruder. Combined with specific additive formulas, a modified material is prepared to improve its performance and dispersion during the blow molding process.
The high performance and stability of the modified material during the blow molding process is achieved, the tensile strength and biodecomposition rate of the film are improved, and the environmentally friendly degradation characteristics are ensured.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fillers for polymer materials, in particular to a modified material and a preparation method thereof and a polybutylene caproate terephthalate film. Background Art
[0002] With the continuous improvement of environmental awareness and the promotion of relevant policies, the demand for degradable plastics will continue to grow. As a biodegradable plastic with excellent performance, polybutylene terephthalate (PBAT) has broad market prospects. In the journal "Guangdong Chemistry", Yang Fan and other authors mentioned in the article "Research Progress and Application of PBAT and Its Modified Composite Materials" that the current application of PBAT is still limited by its high cost, low strength and difficulty in processing, which has prompted researchers to explore various modification technologies to improve its performance and reduce costs.
[0003] Most of the existing technologies still modify PBAT through nanofillers, specifically adding calcium carbonate into the processing of PBAT to reduce the cost of the product. For example, CN118978795A discloses a PBAT resin composite material and a compound fertilizer composition, which consists of 100 parts of degradable resin and 25-28 parts of calcium carbonate by weight; the degradable resin contains PBAT resin, and the weight proportion of PBAT resin in the degradable resin is not less than 90%; the weight average molecular weight of PBAT resin is not less than 60,000; the particle size of calcium carbonate is 1800-2000 mesh. However, its highest tensile strength is only 20.7MPa in Example 4, which still does not meet the tensile strength requirements of some films prepared using PBAT, which will cause it to be damaged during the preparation of the film, reducing production efficiency and causing substantial waste.
[0004] Therefore, in the prior art, calcium carbonate is modified to improve its performance in mixed preparation with PBAT. For example, CN116854993A discloses a filler composition, which is mainly composed of unmodified micron-sized calcium carbonate, and the filler composition contains the following components in mass percentage: (A) 2%-5% of micron-sized calcium carbonate modified with epoxy-polyethylene glycol-epoxy; (B) 2%-5% of micron-sized calcium carbonate modified with polyethylene glycol functionalized biimidazole ionic liquid. However, the introduction of modifiers such as epoxy-polyethylene glycol-epoxy will affect its biodegradability, which will slow down the degradation rate of the modified micron-sized calcium carbonate and PBAT in the natural environment, thereby having a potential impact on the environment. At the same time, the biodegradability of polyethylene glycol functionalized biimidazole ionic liquid is poor, which will also affect the degradation process of the modified micron-sized calcium carbonate in the natural environment. And according to the production of ionic liquids in the prior art, they will have toxic effects on soil microorganisms, aquatic organisms, etc. during use and disposal, affecting the ecological balance. Therefore, this technical solution will cause the degradation rate of degradable PBAT to be greatly reduced after modification. There is also a risk of harming the environment, and it is not suitable for promotion and application.
[0005] Based on the above-mentioned prior art, the prior art still has urgent technical problems to be solved, such as the inability to improve the performance of PBAT and maintain a good biodegradability rate of PBAT while using calcium carbonate to modify PBAT. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a modified material, wherein the modified material is prepared by melt extrusion of polybutylene terephthalate (PBAT), activated micron-sized calcium carbonate and an additive through a twin-screw extruder; the activated micron-sized calcium carbonate is prepared by activating the micron-sized calcium carbonate with a powder activation device by mixing micron-sized calcium carbonate and a silane coupling agent; In terms of weight, the proportions of the components in the modified material are: Polybutylene terephthalate (PBAT): 15-20 parts by weight; Activated micron-sized calcium carbonate: 79-82 parts by weight; Auxiliary agent: 1-3 parts by weight; Wherein, in parts by weight, the proportions of the components in the activated micron-sized calcium carbonate are: Micronized calcium carbonate: 95-99 parts by weight; Silane coupling agent: 1-5 parts by weight; The average particle size of the activated micron-sized calcium carbonate is 2800-3500 meshes.
[0007] Furthermore, the melt index of the polybutylene terephthalate (PBAT) at 190° C. and 2.16 kg is 3-5 g / 10 min.
[0008] Furthermore, the average particle size of the micron-sized calcium carbonate is 2500-3000 meshes.
[0009] Furthermore, the refractive index of the silane coupling agent at 20°C (N D ) is 1.3875, density is 0.985g / ml, viscosity is 4.2mm 2 / S.
[0010] Furthermore, the silane coupling agent is an alkyl-modified polysiloxane.
[0011] Furthermore, the auxiliary agent is composed of a chain extender, a nucleating agent, a lubricant, and an antioxidant; In terms of weight, the proportions of the components in the additive are: Chain extender: 0.2-0.4 parts by weight; Nucleating agent: 0.4-0.6 parts by weight; Lubricant: 0.3-1.2 parts by weight; Antioxidant: 0.1-0.8 parts by weight.
[0012] Furthermore, the chain extender is a copolymer of glycidyl methacrylate (GMA) and alkane.
[0013] Furthermore, the chain extender has a melting point of 96-99° C., a melt index of 200-250 g / 10 min at 190° C. and 2.16 kg, and a mass content of glycidyl methacrylate (GMA) in the chain extender of ≥25%.
[0014] Furthermore, the nucleating agent includes but is not limited to one or more of talc, chalk, mica or silicon oxide.
[0015] Furthermore, the lubricant includes but is not limited to one or more of oleic acid amide, oxidized polyethylene wax, and stearic acid.
[0016] Furthermore, the antioxidant is antioxidant 1010.
[0017] The present invention also provides a method for preparing the modified material, comprising the following steps: Step 1, using a silane coupling agent to activate micron-sized calcium carbonate through a powder activation device to obtain activated micron-sized calcium carbonate; Step 2, adding polybutylene terephthalate (PBAT), activated micron-sized calcium carbonate and additives into a high-speed mixer for mixing and dispersing to obtain a dispersed material; Step 3, placing the dispersed material into a twin-screw extruder for melt extrusion to obtain an extruded material; Step 4: pelletizing and drying the extrudate to obtain the modified material.
[0018] Furthermore, the powder activation device in step 1 includes a feeding system, an activation chamber, and a discharging system in sequence according to the direction of the material, and also includes a temperature control system to control the temperature of the activation chamber.
[0019] Furthermore, the feeding system includes a feeding port, and the discharging system includes a discharging port.
[0020] Furthermore, the feeding sequence of the powder activation device is to first add micron-sized calcium carbonate from the feeding system into the activation chamber, and when the temperature in the activation chamber reaches 50°C, add silane coupling agent from the feeding system into the activation chamber, and control the temperature in the activation chamber to 120°C.
[0021] Furthermore, the silane coupling agent and the micron-sized calcium carbonate are stirred by a stirring blade rotating at a high speed in the activation chamber, the stirring speed is 3500-5000 rad / min, the stirring time is 10-20 min, and the activation is completed after the stirring is completed to obtain the activated micron-sized calcium carbonate, and the powder activation device is sent out from the discharging system.
[0022] Furthermore, in step 2, the rotation speed of the high speed mixer is 750-1440 rad / min, and the mixing time is 30-40 min.
[0023] Furthermore, the twin-screw extruder in step 3 includes seven temperature zones, and the temperatures of each zone are set to 180-190°C in zone 1, 210-220°C in zone 2, 210-220°C in zone 3, 200-210°C in zone 4, 190-195°C in zone 5, 190-195°C in zone 6, and 175-185°C in zone 7, and the screw speed of the twin-screw extruder is 200-220r / min.
[0024] Furthermore, the equipment used for pelletizing in step 4 is a pelletizer.
[0025] Furthermore, in step 4, the drying temperature is 90-100° C. and the drying time is 1-2 h.
[0026] The present invention also provides a degradable masterbatch, wherein the raw materials for preparing the degradable masterbatch include modified materials.
[0027] The present invention also provides a polybutylene caproate terephthalate film, which is prepared by reacting the modified material or degradation masterbatch with polybutylene caproate terephthalate (PBAT) through a single screw film blowing machine; The mass ratio of the modified material or the degradation masterbatch to polybutylene terephthalate (PBAT) is (5-7): (3-5); The polybutylene caproate terephthalate film has a heat sealing strength of 9-10N, a transverse elongation at break of 527-672%, a transverse tensile strength of 21.43-32.35Mpa, a longitudinal elongation at break of 501-576%, and a longitudinal tensile strength of 20.85-31.35Mpa.
[0028] Furthermore, in a biodegradability test using a thin layer of cellulose as a reference material, the relative biodegradability of the poly(butylene caproate terephthalate) film at 180 days is greater than 98%.
[0029] The present invention also provides a method for preparing the polybutylene caproate terephthalate film, wherein the modified material or degradation masterbatch is added together with polybutylene caproate terephthalate (PBAT) into the single-screw film blowing machine, and the film is obtained by heating and melting, extruding and blowing, and cooling and solidifying.
[0030] Furthermore, the single screw extruder contained in the single screw film blowing machine includes five heating temperature zones, and the temperature of each zone is set to 140-155°C in zone one, 150-165°C in zone two, 160-175°C in zone three, 160-170°C in zone four, and 150-160°C in zone five.
[0031] Furthermore, the blow-up ratio (BUR) of the single-screw film blowing machine is 2-3.
[0032] Furthermore, the modified material or degradation masterbatch and polybutylene terephthalate are added into the single-screw film blowing machine, and are pushed to the heating temperature zone as the screw rotates, and are heated to a molten state in the heating temperature zone. At the same time, the raw materials are sheared and squeezed by the screw to form a flowable melt; The melt is extruded through the extruder head of the single-screw film blowing machine under the push of the screw, and then the extruded melt is blown into a film through the blowing device of the single-screw film blowing machine. During the blowing process, the blowing ratio is controlled, and finally the film is cooled and solidified by water cooling or air cooling to obtain the polybutylene terephthalate film.
[0033] The beneficial effects of the present invention are: 1. The present invention provides a modified material, wherein the modified material is prepared by melt extrusion of polybutylene terephthalate (PBAT), activated micron-sized calcium carbonate, and an additive through a twin-screw extruder; the activated micron-sized calcium carbonate is prepared by activating micron-sized calcium carbonate with a silane coupling agent through a powder activation device; because a film with good dispersion and stable performance cannot be obtained when the traditional calcium carbonate powder is mixed with PBAT and then blow-molded, the present invention modifies the powder from multiple angles, firstly by selecting calcium carbonate with a specific particle size, grafting the silane coupling agent onto the micron-sized calcium carbonate through activation, and then the activated micron-sized calcium carbonate is activated with the PBAT raw material. In melt blending and extrusion, PBAT is equivalent to a carrier. On the one hand, it prevents calcium carbonate from being in powder form. When mixed with a large amount of PBAT for blow molding in the later stage, the powdered calcium carbonate is not easy to disperse. By fusing it with calcium carbonate through a specific raw material formula and process to form a modified material as a whole granular material, the above problem can be completely avoided. On the other hand, in the mixing process, the present invention selects a specific auxiliary agent formula. While various auxiliary agents play their own roles, they also directly react physically or chemically with other raw materials or auxiliary agents, once again strengthening the bonding strength of calcium carbonate and PBAT, providing a more stable modified material for subsequent blow molding film formation, and finally achieving the purpose of improving the overall performance of the blow molding product. 2. In the present invention, the stirring blades of the silane coupling agent and the micron-sized calcium carbonate in the activation chamber rotate and stir at a high speed, so that the particles of the micron-sized calcium carbonate generate intense friction and collision. In this process, the surface energy of the micron-sized calcium carbonate particles increases, and the particles originally agglomerated together are broken up, thereby increasing the specific surface area of the micron-sized calcium carbonate. The adsorption layer on the surface of the micron-sized calcium carbonate particles can be destroyed by physical activation, exposing more hydroxyl active sites. Therefore, the inorganic groups contained in the silane coupling agent can fully combine with the hydroxyl groups exposed on the surface of the micron-sized calcium carbonate to form stable chemical bonds, thereby improving the dispersibility of the micron-sized calcium carbonate and the compatibility of subsequent raw material mixing; At the same time, after ensuring that the temperature of micron-sized calcium carbonate reaches 50°C, the micron-sized calcium carbonate obtains sufficient energy, and then the silane coupling agent is added, and the temperature is raised to 120°C, the thermal motion ability of its internal atoms and molecules is fully improved. On the one hand, it is helpful to desorb impurities such as gas and moisture adsorbed on the surface of micron-sized calcium carbonate, clean the surface of the powder, and expose more active sites; on the other hand, it can promote the structural adjustment and chemical reaction inside the micron-sized calcium carbonate and the silane coupling agent, so as to improve the overall activity and make it easier to activate; Finally, under the high temperature environment of the twin-screw extruder, PBAT changes from a solid state to a molten state, and its molecular chains begin to move violently and entangle with each other. In this process, the silane coupling agent in the activated micron-sized calcium carbonate can directly react chemically with the groups on the PBAT molecular chain, such as hydroxyl and carboxyl groups, to form stable chemical bonds, thereby enhancing the interfacial bonding force between the micron-sized calcium carbonate and PBAT. At the same time, under the shearing action of the twin-screw extruder, the activated micron-sized calcium carbonate can also obtain better dispersibility in PBAT, and some of the original tiny agglomerates are gradually broken up, so that the activated micron-sized calcium carbonate can more fully play its reinforcing and filling roles. 3. The present invention uses an existing powder activation device, sets specific activation process parameters, and selects the ratio and type of raw materials to obtain an average particle size (2800-3500 mesh) of activated micron-sized calcium carbonate that is close to the average particle size (2500-3000 mesh) of the raw material micron-sized calcium carbonate. This proves that the activated micron-sized calcium carbonate prepared by the present invention has good dispersibility, because poorly dispersed calcium carbonate may agglomerate due to poor dispersibility, resulting in uneven particle size distribution, thereby affecting the performance of modified materials prepared with raw materials such as PBAT in the later stage; 4. In addition, the present invention further enhances and modifies PBAT from multiple microscopic perspectives through specially selected auxiliary agents (chain extenders, nucleating agents, lubricants, antioxidants). For example, the chain extender can react with the carboxyl and hydroxyl groups in polybutylene terephthalate (PBAT) to increase the molecular weight and melt viscosity; on the other hand, there is an internal plasticization phenomenon in polybutylene terephthalate (PBAT). By reacting with the hydroxyl groups contained therein, a flexible chain segment is introduced into the rigid chain, so that the mobility of the molecular chain is enhanced, which plays the role of internal plasticization; The nucleating agent acts as a crystal nucleus in the molten polybutylene terephthalate (PBAT), inducing the PBAT molecular chain to crystallize around it. During the extrusion process of the twin-screw extruder, as the temperature changes, the PBAT molecular chain begins to be orderly arranged on the surface of the crystal nucleus provided by the nucleating agent to form a crystallized region, thereby improving the crystallinity of the PBAT modified filler; The lubricant can form a lubricating film between the molten polybutylene terephthalate (PBAT) and the screw of the twin-screw extruder, the barrel wall and the polybutylene terephthalate (PBAT) molecular chain, which helps to reduce the viscosity of the melt, reduce friction, and make the material conveyed in the twin-screw extruder smoother. The lubricating film formed between the polybutylene terephthalate (PBAT) molecular chains can also improve the sliding properties between the PBAT molecular chains, and improve the sliding properties between the PBAT molecular chains and other materials, so that all the raw materials are fully dispersed during the extrusion process; The antioxidant can capture free radicals generated by the molten polybutylene terephthalate (PBAT) during high-temperature extrusion of the twin-screw extruder, inhibit the occurrence of oxidation reactions, prevent its degradation, and help maintain the stability of the raw materials and related mechanical properties; 5. The polybutylene terephthalate film prepared by the modified material or the degradation masterbatch through a single screw film blowing machine has a heat sealing strength of 9-10N, a transverse elongation at break of 527-672%, a transverse tensile strength of 21.43-32.35Mpa, a longitudinal elongation at break of 501-576%, and a longitudinal tensile strength of 20.85-31.35Mpa, which are better than the film performance obtained by adding the commercially available modified material to PBAT. DETAILED DESCRIPTION
[0034] Examples 1-4 are modified materials and preparation methods thereof; Examples 5-8 are polybutylene terephthalate films prepared using the modified materials prepared in Examples 1-4 as raw materials.
[0035] Example 1 This embodiment provides a modified material and a preparation method thereof, wherein the modified material is prepared by melt extrusion of polybutylene hexanoate terephthalate (PBAT), activated micron-sized calcium carbonate, and an additive through a twin-screw extruder; the activated micron-sized calcium carbonate is prepared by activating micron-sized calcium carbonate with a silane coupling agent through a powder activation device; In terms of weight, the proportions of the components in the modified material are: Polybutylene terephthalate (PBAT): 18 parts by weight; Activated micron-sized calcium carbonate: 80 parts by weight; Auxiliary agent: 2 parts by weight; Wherein, in parts by weight, the proportions of the components in the activated micron-sized calcium carbonate are: Micronized calcium carbonate: 98 parts by weight; Silane coupling agent: 2 parts by weight; The average particle size of the activated micron-sized calcium carbonate is 3200 meshes.
[0036] The polybutylene terephthalate (PBAT) has a melt index of 3 g / 10 min at 190° C. and 2.16 kg.
[0037] The average particle size of the micron-sized calcium carbonate is 3000 meshes.
[0038] The refractive index of the silane coupling agent at 20°C (N D ) is 1.3875, density is 0.985g / ml, viscosity is 4.2mm 2 / S, specifically, in this embodiment, the silane coupling agent is an alkyl-modified polysiloxane purchased from Zhejiang Feidian Chemical Co., Ltd., model FD-1106; In some embodiments, as long as the refractive index, density, and viscosity of the silane coupling agent meet the corresponding index requirements, it can be used.
[0039] The auxiliary agent is composed of a chain extender, a nucleating agent, a lubricant, and an antioxidant; In terms of weight, the proportions of the components in the additive are: Chain extender: 0.3 parts by weight; wherein the chain extender is a copolymer of glycidyl methacrylate (GMA) and alkane, the melting point of the chain extender is 98°C, the melt index at 190°C and 2.16kg is 230g / 10min, and the mass content of glycidyl methacrylate (GMA) in the chain extender is 30%.
[0040] Nucleating agent is talcum powder: 0.5 parts by weight; The lubricant is oleic acid amide: 1.0 parts by weight; The antioxidant is antioxidant 1010: 0.2 parts by weight.
[0041] The preparation method of the modified material of this embodiment comprises the following steps: Step 1, using a silane coupling agent to activate micron-sized calcium carbonate through a powder activation device to obtain activated micron-sized calcium carbonate; The powder activation device includes a feeding system, an activation chamber, and a discharging system in sequence according to the direction of the material, and also includes a temperature control system to control the temperature of the activation chamber; In this embodiment, the feed system is a feed inlet, and the discharge system is a discharge outlet; The feeding sequence of the powder activation device is to first add micron-sized calcium carbonate from the feeding system into the activation chamber, and when the temperature in the activation chamber reaches 50°C, add silane coupling agent from the feeding system into the activation chamber, and control the temperature in the activation chamber to be 120°C.
[0042] The silane coupling agent and the micron-sized calcium carbonate are stirred by a stirring blade rotating at a high speed in the activation chamber, the stirring speed is 4000 rad / min, the stirring time is 20 min, and after the stirring is completed, the activation is completed to obtain the activated micron-sized calcium carbonate, and the powder activation device is sent out from the discharging system; Step 2, adding polybutylene terephthalate (PBAT), activated micron-sized calcium carbonate and additives into a high-speed mixer for mixing and dispersing to obtain a dispersed material; Wherein, the speed of the high-speed mixer is 1200 rad / min, and the mixing time is 30 min; Step 3, placing the dispersed material into a twin-screw extruder for melt extrusion to obtain an extruded material; The twin-screw extruder includes seven temperature zones, and the temperatures of the zones are set to 190°C for zone 1, 210°C for zone 2, 220°C for zone 3, 210°C for zone 4, 195°C for zone 5, 190°C for zone 6, and 185°C for zone 7. The screw speed of the twin-screw extruder is 200r / min. Step 4: pelletize the extruded material using a pelletizer, and then dry it at 100° C. for 1.5 hours to obtain the modified material.
[0043] Example 2 This embodiment provides a modified material and a preparation method thereof, wherein the modified material is prepared by melt extrusion of polybutylene hexanoate terephthalate (PBAT), activated micron-sized calcium carbonate, and an additive through a twin-screw extruder; the activated micron-sized calcium carbonate is prepared by activating micron-sized calcium carbonate with a silane coupling agent through a powder activation device; In terms of weight, the proportions of the components in the modified material are: Polybutylene terephthalate (PBAT): 15 parts by weight; Activated micron-sized calcium carbonate: 82 parts by weight; Auxiliary agent: 3 parts by weight; Wherein, in terms of weight, the proportions of the components in the activated micron-sized calcium carbonate are: Micronized calcium carbonate: 95 parts by weight; Silane coupling agent: 5 parts by weight; The average particle size of the activated micron-sized calcium carbonate is 2800 meshes.
[0044] The polybutylene terephthalate (PBAT) has a melt index of 4 g / 10 min at 190° C. and 2.16 kg.
[0045] The average particle size of the micron-sized calcium carbonate is 2500 meshes.
[0046] The refractive index of the silane coupling agent at 20°C (N D ) is 1.3875, density is 0.985g / ml, viscosity is 4.2mm 2 / S, specifically, in this embodiment, the silane coupling agent is an alkyl-modified polysiloxane purchased from Zhejiang Feidian Chemical Co., Ltd., model FD-1106; In some embodiments, as long as the refractive index, density, and viscosity of the silane coupling agent meet the corresponding index requirements, it can be used.
[0047] The auxiliary agent is composed of a chain extender, a nucleating agent, a lubricant, and an antioxidant; In terms of weight, the proportions of the components in the additive are: Chain extender: 0.4 parts by weight; wherein the chain extender is a copolymer of glycidyl methacrylate (GMA) and alkane, the melting point of the chain extender is 98°C, the melt index at 190°C and 2.16kg is 200g / 10min, and the mass content of glycidyl methacrylate (GMA) in the chain extender is 25%.
[0048] Nucleating agent is chalk: 0.6 parts by weight; The lubricant is oleic acid amide: 1.2 parts by weight; The antioxidant is antioxidant 1010: 0.8 parts by weight.
[0049] The preparation method of the modified material of this embodiment comprises the following steps: Step 1, using a silane coupling agent to activate micron-sized calcium carbonate through a powder activation device to obtain activated micron-sized calcium carbonate; The powder activation device includes a feeding system, an activation chamber, and a discharging system in sequence according to the direction of the material, and also includes a temperature control system to control the temperature of the activation chamber; In this embodiment, the feed system is a feed inlet, and the discharge system is a discharge outlet; The feeding sequence of the powder activation device is to first add micron-sized calcium carbonate from the feeding system into the activation chamber, and when the temperature in the activation chamber reaches 50°C, add silane coupling agent from the feeding system into the activation chamber, and control the temperature in the activation chamber to be 120°C.
[0050] The silane coupling agent and the micron-sized calcium carbonate are stirred by a stirring blade in the activation chamber at a high speed, the stirring speed is 3500 rad / min, the stirring time is 20 min, and after the stirring is completed, the activation is completed to obtain the activated micron-sized calcium carbonate, and the powder activation device is sent out from the discharging system; Step 2, adding polybutylene terephthalate (PBAT), activated micron-sized calcium carbonate and additives into a high-speed mixer for mixing and dispersing to obtain a dispersed material; Wherein, the speed of the high speed mixer is 1440rad / min, and the mixing time is 35min; Step 3, placing the dispersed material into a twin-screw extruder for melt extrusion to obtain an extruded material; The twin-screw extruder includes seven temperature zones, and the temperatures of the zones are set to 180°C for zone 1, 210°C for zone 2, 210°C for zone 3, 200°C for zone 4, 195°C for zone 5, 195°C for zone 6, and 180°C for zone 7. The screw speed of the twin-screw extruder is 220r / min. Step 4: pelletize the extruded material using a pelletizer, and then dry it at 95° C. for 2 hours to obtain the modified material.
[0051] Example 3 This embodiment provides a modified material and a preparation method thereof, wherein the modified material is prepared by melt extrusion of polybutylene hexanoate terephthalate (PBAT), activated micron-sized calcium carbonate, and an additive through a twin-screw extruder; the activated micron-sized calcium carbonate is prepared by activating micron-sized calcium carbonate with a silane coupling agent through a powder activation device; In terms of weight, the proportions of the components in the modified material are: Polybutylene terephthalate (PBAT): 20 parts by weight; Activated micron-sized calcium carbonate: 79 parts by weight; Auxiliary agent: 1 part by weight; Wherein, in terms of weight, the proportions of the components in the activated micron-sized calcium carbonate are: Micronized calcium carbonate: 99 parts by weight; Silane coupling agent: 1 part by weight; The average particle size of the activated micron-sized calcium carbonate is 3500 meshes.
[0052] The polybutylene terephthalate (PBAT) has a melt index of 5 g / 10 min at 190° C. and 2.16 kg.
[0053] The average particle size of the micron-sized calcium carbonate is 3000 meshes.
[0054] The refractive index of the silane coupling agent at 20°C (N D ) is 1.3875, density is 0.985g / ml, viscosity is 4.2mm 2 / S, specifically, in this embodiment, the silane coupling agent is an alkyl-modified polysiloxane purchased from Zhejiang Feidian Chemical Co., Ltd., model FD-1106; In some embodiments, as long as the refractive index, density, and viscosity of the silane coupling agent meet the corresponding index requirements, it can be used.
[0055] The auxiliary agent is composed of a chain extender, a nucleating agent, a lubricant, and an antioxidant; In terms of weight, the proportions of the components in the additive are: Chain extender: 0.2 parts by weight; wherein the chain extender is a copolymer of glycidyl methacrylate (GMA) and alkane, the melting point of the chain extender is 98°C, the melt index at 190°C and 2.16kg is 250g / 10min, and the mass content of glycidyl methacrylate (GMA) in the chain extender is 35%.
[0056] Nucleating agent is mica: 0.4 parts by weight; The lubricant is stearic acid: 0.3 parts by weight; The antioxidant is antioxidant 1010: 0.1 parts by weight.
[0057] The preparation method of the modified material of this embodiment comprises the following steps: Step 1, using a silane coupling agent to activate micron-sized calcium carbonate through a powder activation device to obtain activated micron-sized calcium carbonate; The powder activation device includes a feeding system, an activation chamber, and a discharging system in sequence according to the direction of the material, and also includes a temperature control system to control the temperature of the activation chamber; In this embodiment, the feed system is a feed inlet, and the discharge system is a discharge outlet; The feeding sequence of the powder activation device is to first add micron-sized calcium carbonate from the feeding system into the activation chamber, and when the temperature in the activation chamber reaches 50°C, add silane coupling agent from the feeding system into the activation chamber, and control the temperature in the activation chamber to be 120°C.
[0058] The silane coupling agent and the micron-sized calcium carbonate are stirred by a stirring blade rotating at a high speed in the activation chamber, the stirring speed is 5000 rad / min, the stirring time is 10 min, and after the stirring is completed, the activation is completed to obtain the activated micron-sized calcium carbonate, and the powder activation device is sent out from the discharging system; Step 2, adding polybutylene terephthalate (PBAT), activated micron-sized calcium carbonate and additives into a high-speed mixer for mixing and dispersing to obtain a dispersed material; Wherein, the rotation speed of the high speed mixer is 750rad / min, and the mixing time is 40min; Step 3, placing the dispersed material into a twin-screw extruder for melt extrusion to obtain an extruded material; The twin-screw extruder includes seven temperature zones, and the temperatures of the zones are set to 180°C for zone 1, 220°C for zone 2, 220°C for zone 3, 210°C for zone 4, 190°C for zone 5, 190°C for zone 6, and 175°C for zone 7. The screw speed of the twin-screw extruder is 210r / min. Step 4: pelletize the extruded material using a pelletizer, and then dry it at 90° C. for 1 hour to obtain the modified material.
[0059] Example 4 This embodiment provides a modified material and a preparation method thereof, wherein the modified material is prepared by melt extrusion of polybutylene hexanoate terephthalate (PBAT), activated micron-sized calcium carbonate, and an additive through a twin-screw extruder; the activated micron-sized calcium carbonate is prepared by activating micron-sized calcium carbonate with a silane coupling agent through a powder activation device; In terms of weight, the proportions of the components in the modified material are: Polybutylene terephthalate (PBAT): 19 parts by weight; Activated micron-sized calcium carbonate: 80 parts by weight; Auxiliary agent: 1 part by weight; Wherein, in terms of weight, the proportions of the components in the activated micron-sized calcium carbonate are: Micronized calcium carbonate: 97 parts by weight; Silane coupling agent: 3 parts by weight; The average particle size of the activated micron-sized calcium carbonate is 3400 meshes.
[0060] The polybutylene terephthalate (PBAT) has a melt index of 4 g / 10 min at 190° C. and 2.16 kg.
[0061] The average particle size of the micron-sized calcium carbonate is 3000 meshes.
[0062] The refractive index of the silane coupling agent at 20°C (N D ) is 1.3875, density is 0.985g / ml, viscosity is 4.2mm 2 / S, specifically, in this embodiment, the silane coupling agent is an alkyl-modified polysiloxane purchased from Zhejiang Feidian Chemical Co., Ltd., model FD-1106; In some embodiments, as long as the refractive index, density, and viscosity of the silane coupling agent meet the corresponding index requirements, it can be used.
[0063] The auxiliary agent is composed of a chain extender, a nucleating agent, a lubricant, and an antioxidant; In terms of weight, the proportions of the components in the additive are: Chain extender: 0.2 parts by weight; wherein the chain extender is a copolymer of glycidyl methacrylate (GMA) and alkane, the melting point of the chain extender is 98°C, the melt index at 190°C and 2.16kg is 250g / 10min, and the mass content of glycidyl methacrylate (GMA) in the chain extender is 35%.
[0064] Nucleating agent is silicon oxide: 0.4 parts by weight; The lubricant is oxidized polyethylene wax: 0.3 parts by weight; The antioxidant is antioxidant 1010: 0.1 parts by weight.
[0065] The preparation method of the modified material of this embodiment comprises the following steps: Step 1, using a silane coupling agent to activate micron-sized calcium carbonate through a powder activation device to obtain activated micron-sized calcium carbonate; The powder activation device includes a feeding system, an activation chamber, and a discharging system in sequence according to the direction of the material, and also includes a temperature control system to control the temperature of the activation chamber; In this embodiment, the feed system is a feed inlet, and the discharge system is a discharge outlet; The feeding sequence of the powder activation device is to first add micron-sized calcium carbonate from the feeding system into the activation chamber, and when the temperature in the activation chamber reaches 50°C, add silane coupling agent from the feeding system into the activation chamber, and control the temperature in the activation chamber to be 120°C.
[0066] The silane coupling agent and the micron-sized calcium carbonate are stirred by a stirring blade rotating at a high speed in the activation chamber, the stirring speed is 5000 rad / min, the stirring time is 10 min, and after the stirring is completed, the activation is completed to obtain the activated micron-sized calcium carbonate, and the powder activation device is sent out from the discharging system; Step 2, adding polybutylene terephthalate (PBAT), activated micron-sized calcium carbonate and additives into a high-speed mixer for mixing and dispersing to obtain a dispersed material; Wherein, the speed of the high-speed mixer is 1300 rad / min, and the mixing time is 35 min; Step 3, placing the dispersed material into a twin-screw extruder for melt extrusion to obtain an extruded material; The twin-screw extruder includes seven temperature zones, and the temperatures of the zones are set to 180°C for zone 1, 210°C for zone 2, 220°C for zone 3, 210°C for zone 4, 195°C for zone 5, 190°C for zone 6, and 175°C for zone 7. The screw speed of the twin-screw extruder is 210r / min. Step 4: pelletize the extruded material using a pelletizer, and then dry it at 100° C. for 1 hour to obtain the modified material.
[0067] Example 5 This embodiment uses the modified material prepared in Example 1 as a degradation masterbatch to prepare a polybutylene terephthalate film, specifically, the degradation masterbatch and polybutylene terephthalate (PBAT) are prepared by a single-screw film blowing machine; The mass ratio of the degradation masterbatch to polybutylene terephthalate (PBAT) is 6:4; The polybutylene caproate terephthalate film has a heat sealing strength of 9N, a transverse elongation at break of 606%, a transverse tensile strength of 28.63 MPa, a longitudinal elongation at break of 516%, and a longitudinal tensile strength of 27.18 MPa.
[0068] In this embodiment, the method for preparing the polybutylene terephthalate film is specifically to add the above-mentioned degradation masterbatch and polybutylene terephthalate (PBAT) into the single-screw film blowing machine, and obtain the film by heating and melting, extruding and blowing, and cooling and solidifying.
[0069] The single screw extruder contained in the single screw film blowing machine includes five heating temperature zones, and the temperature of each zone is set to 140°C in zone one, 150°C in zone two, 160°C in zone three, 160°C in zone four, and 160°C in zone five.
[0070] The single screw film blowing machine has a blow-up ratio (BUR) of 2.
[0071] In this embodiment, the degradation masterbatch and PBAT are added to the single-screw film blowing machine, and are pushed to the heating temperature zone as the screw rotates. In the heating temperature zone, they are heated to a molten state, and at the same time, the raw materials are sheared and squeezed by the screw to form a flowable melt; The melt is extruded through the extruder head of the single-screw film blowing machine under the push of the screw, and then the extruded melt is blown into a film through the blowing device of the single-screw film blowing machine. During the blowing process, the blowing ratio is controlled, and finally the film is cooled and solidified by water cooling to room temperature to obtain the polybutylene terephthalate film.
[0072] Example 6 This embodiment uses the modified material prepared in Example 2 as a degradation masterbatch to prepare a polybutylene terephthalate film, specifically, the degradation masterbatch and polybutylene terephthalate (PBAT) are prepared by a single-screw film blowing machine; The mass ratio of the degradation masterbatch to polybutylene terephthalate (PBAT) is 7:3; The polybutylene caproate terephthalate film has a heat sealing strength of 10N, a transverse elongation at break of 672%, a transverse tensile strength of 32.35 MPa, a longitudinal elongation at break of 576%, and a longitudinal tensile strength of 31.35 MPa.
[0073] In this embodiment, the method for preparing the polybutylene terephthalate film is specifically to add the above-mentioned degradation masterbatch and polybutylene terephthalate (PBAT) into the single-screw film blowing machine, and obtain the film by heating and melting, extruding and blowing, and cooling and solidifying.
[0074] The single screw extruder contained in the single screw film blowing machine includes five heating temperature zones, and the temperature of each zone is set to 150°C for zone one, 160°C for zone two, 170°C for zone three, 165°C for zone four, and 150°C for zone five.
[0075] The single screw film blowing machine has a blow-up ratio (BUR) of 2.
[0076] In this embodiment, the degradation masterbatch and PBAT are added to the single-screw film blowing machine, and are pushed to the heating temperature zone as the screw rotates. In the heating temperature zone, they are heated to a molten state, and at the same time, the raw materials are sheared and squeezed by the screw to form a flowable melt; The melt is extruded through the extruder head of the single-screw film blowing machine under the push of the screw, and then the extruded melt is blown into a film through the blowing device of the single-screw film blowing machine. During the blowing process, the blowing ratio is controlled, and finally the film is cooled and solidified by water cooling to room temperature to obtain the polybutylene terephthalate film.
[0077] Example 7 This embodiment uses the modified material prepared in Example 3 as a degradation masterbatch to prepare a polybutylene terephthalate film, specifically, the degradation masterbatch and polybutylene terephthalate (PBAT) are prepared by a single-screw film blowing machine; The mass ratio of the degradation masterbatch to polybutylene terephthalate (PBAT) is 5.5:4.5; The polybutylene caproate terephthalate film has a heat sealing strength of 9N, a transverse elongation at break of 560%, a transverse tensile strength of 27.72 MPa, a longitudinal elongation at break of 512%, and a longitudinal tensile strength of 26.56 MPa.
[0078] In this embodiment, the method for preparing the polybutylene terephthalate film is specifically to add the above-mentioned degradation masterbatch and polybutylene terephthalate (PBAT) into the single-screw film blowing machine, and obtain the film by heating and melting, extruding and blowing, and cooling and solidifying.
[0079] The single screw extruder contained in the single screw film blowing machine includes five heating temperature zones, and the temperature of each zone is set to 155°C in zone one, 165°C in zone two, 175°C in zone three, 170°C in zone four, and 160°C in zone five.
[0080] The single screw film blowing machine has a blow-up ratio (BUR) of 3.
[0081] In this embodiment, the degradation masterbatch and PBAT are added to the single-screw film blowing machine, and are pushed to the heating temperature zone as the screw rotates. In the heating temperature zone, they are heated to a molten state, and at the same time, the raw materials are sheared and squeezed by the screw to form a flowable melt; The melt is extruded through the extruder head of the single-screw film blowing machine under the push of the screw, and then the extruded melt is blown into a film through the blowing device of the single-screw film blowing machine. During the blowing process, the blowing ratio is controlled, and finally the film is cooled and solidified by air cooling to room temperature to obtain the polybutylene terephthalate film.
[0082] Example 8 This embodiment uses the modified material prepared in Example 4 as a degradation masterbatch to prepare a polybutylene terephthalate film, specifically, the degradation masterbatch and polybutylene terephthalate (PBAT) are prepared by a single-screw film blowing machine; The mass ratio of the degradation masterbatch to polybutylene terephthalate (PBAT) is 5:5; The polybutylene caproate terephthalate film has a heat sealing strength of 9N, a transverse elongation at break of 527%, a transverse tensile strength of 21.43 MPa, a longitudinal elongation at break of 501%, and a longitudinal tensile strength of 20.85 MPa.
[0083] In this embodiment, the method for preparing the polybutylene terephthalate film is specifically to add the above-mentioned degradation masterbatch and polybutylene terephthalate (PBAT) into the single-screw film blowing machine, and obtain the film by heating and melting, extruding and blowing, and cooling and solidifying.
[0084] The single screw extruder contained in the single screw film blowing machine includes five heating temperature zones, and the temperatures of the zones are respectively set to 155°C for zone one, 165°C for zone two, 170°C for zone three, 170°C for zone four, and 155°C for zone five.
[0085] The single screw film blowing machine has a blow-up ratio (BUR) of 3.
[0086] In this embodiment, the degradation masterbatch and PBAT are added to the single-screw film blowing machine, and are pushed to the heating temperature zone as the screw rotates. In the heating temperature zone, they are heated to a molten state, and at the same time, the raw materials are sheared and squeezed by the screw to form a flowable melt; The melt is extruded through the extruder head of the single-screw film blowing machine under the push of the screw, and then the extruded melt is blown into a film through the blowing device of the single-screw film blowing machine. During the blowing process, the blowing ratio is controlled, and finally the film is cooled and solidified by air cooling to room temperature to obtain the polybutylene terephthalate film.
[0087] Comparative Example 1 The average particle size of the micron-sized calcium carbonate selected in this comparative example is 2000 mesh relative to Example 1. Under the condition that other conditions remain unchanged, a modified filler is provided, wherein the activated micron-sized calcium carbonate obtained in this comparative example agglomerates, and the average particle size cannot be accurately determined.
[0088] Comparative Example 2 In this comparative example, the average particle size of the micron-sized calcium carbonate selected in Example 2 is 4000 mesh. Under the condition that other conditions remain unchanged, a modified filler is provided, wherein the average particle size of the activated micron-sized calcium carbonate obtained in this comparative example is 6000 mesh.
[0089] Comparative Example 3 Compared with Example 3, the auxiliary agents selected in this comparative example only include chain extenders and nucleating agents, and do not include lubricants and antioxidants. In terms of weight parts, chain extenders: 0.5 weight parts; nucleating agents: 0.5 weight parts; when other conditions remain unchanged, a modified filler is provided.
[0090] Comparative Example 4 The refractive index (N) of the silane coupling agent selected in this comparative example at 20°C is D ) is 1.4260, density is 1.069g / ml, viscosity is 3mm 2 / S; specifically, in this comparative example, the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; while other conditions remain unchanged, a modified filler is provided.
[0091] Comparative Example 5 The degradation masterbatch used in this comparative example is commercially available from Dongguan Caijian Plastic Products Co., Ltd., with the brand name MK2740.
[0092] Comparative Example 6 This comparative example is to use the modified filler in comparative example 1 as a degradation masterbatch to replace the degradation masterbatch in example 5, and provide a polybutylene terephthalate film under the condition that other conditions remain unchanged; In this comparative example, the heat sealing strength of the polybutylene terephthalate film is 9N, the transverse elongation at break is 433%, the transverse tensile strength is 19.78 MPa, the longitudinal elongation at break is 389%, and the longitudinal tensile strength is 18.32 MPa.
[0093] Comparative Example 7 This comparative example is to use the modified filler in comparative example 2 as the degradation masterbatch to replace the degradation masterbatch in example 5, and provide a polybutylene terephthalate film under the condition that other conditions remain unchanged; In this comparative example, the heat sealing strength of the polybutylene terephthalate film is 10N, the transverse elongation at break is 514%, the transverse tensile strength is 24.56Mpa, the longitudinal elongation at break is 425%, and the longitudinal tensile strength is 22.91Mpa.
[0094] Comparative Example 8 This comparative example is to use the modified filler in comparative example 3 as the degradation masterbatch to replace the degradation masterbatch in example 6, and provide a polybutylene terephthalate film under the condition that other conditions remain unchanged; In this comparative example, the heat sealing strength of the polybutylene terephthalate film is 8N, the transverse elongation at break is 415%, the transverse tensile strength is 18.74 MPa, the longitudinal elongation at break is 375%, and the longitudinal tensile strength is 17.58 MPa.
[0095] Comparative Example 9 This comparative example is to use the modified filler in comparative example 4 as the degradation masterbatch to replace the degradation masterbatch in example 7, and provide a polybutylene terephthalate film under the condition that other conditions remain unchanged; In this comparative example, the heat sealing strength of the polybutylene terephthalate film is 7N, the transverse elongation at break is 323%, the transverse tensile strength is 16.20 MPa, the longitudinal elongation at break is 276%, and the longitudinal tensile strength is 14.97 MPa.
[0096] Comparative Example 10 This comparative example is to replace the degradation masterbatch in Example 8 with the degradation masterbatch in Comparative Example 5, and provide a polybutylene terephthalate film under the condition that other conditions remain unchanged; In this comparative example, the heat sealing strength of the polybutylene terephthalate film is 7N, the transverse elongation at break is 408%, the transverse tensile strength is 15.93 MPa, the longitudinal elongation at break is 351%, and the longitudinal tensile strength is 20.65 MPa.
[0097] The properties of the polybutylene terephthalate films prepared in Examples 5-8 and Comparative Examples 6-10 are compared, and the comparison results are shown in Table 1: Table 1 Comparison of properties of polybutylene terephthalate films prepared in Examples 5-8 and Comparative Examples 6-10
[0098] At the same time, the relative biodegradability of the polybutylene caproate terephthalate films prepared in Examples 5-8 and Comparative Examples 6-10 was determined. TLC grade cellulose was selected as the reference material. The treatment methods of the reference material and the polybutylene caproate terephthalate film were the same, and both were tested using a degradation instrument in accordance with GB / T 19277.1-2011. The percentage of the biodegradability of the polybutylene caproate terephthalate film and the biodegradability of the reference material was the relative biodegradability of the polybutylene caproate terephthalate film. The biodegradability of the reference material at 180 days was 88.2%. The biodegradability and relative biodegradability of the polybutylene caproate terephthalate films prepared in Examples 5-8 and Comparative Examples 6-10 at 180 days are shown in Table 2: Table 2 Biodegradation rate and relative biodegradation rate of polybutylene terephthalate films prepared in Examples 5-8 and Comparative Examples 6-10
[0099] By comparison, it can be seen that the present invention modifies the powder from multiple angles. First, by selecting calcium carbonate of a specific particle size, the silane coupling agent is grafted onto the micron-sized calcium carbonate by activation, and then the activated micron-sized calcium carbonate is melt-blended and extruded with the PBAT raw material. At this time, the PBAT is equivalent to a carrier. On the one hand, it prevents the calcium carbonate from being in powder form. When mixed with a large amount of PBAT for blow molding in the later stage, the powdered calcium carbonate is not easy to disperse. After it is fused with calcium carbonate through a specific raw material formula and process to form a modified material as a whole granular material, the above problem can be completely avoided; on the other hand, in the mixing process, the present invention selects a specific auxiliary agent formula. While various auxiliary agents play their own roles, they also directly react physically or chemically with other raw materials or auxiliary agents, once again strengthening the bonding strength of calcium carbonate and PBAT, providing a more stable modified material for subsequent blow molding film, and finally achieving the purpose of improving the overall performance of the blow molded product; at the same time, the film performance is better than that obtained by adding the commercially available modified material to PBAT, and the relative biodegradability rate is higher, both of which are greater than 98%.
[0100] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A modified material, characterized in that: The modified material is prepared by melt extrusion of polybutylene caproate terephthalate, activated micron-sized calcium carbonate and additives through a twin-screw extruder; the activated micron-sized calcium carbonate is prepared by activating micron-sized calcium carbonate with a silane coupling agent through a powder activation device; In terms of weight, the proportions of the components in the modified material are: Polybutylene terephthalate: 15-20 parts by weight; Activated micron-sized calcium carbonate: 79-82 parts by weight; Auxiliary agent: 1-3 parts by weight; Wherein, in parts by weight, the proportions of the components in the activated micron-sized calcium carbonate are: Micronized calcium carbonate: 95-99 parts by weight; Silane coupling agent: 1-5 parts by weight; The average particle size of the activated micron-sized calcium carbonate is 2800-3500 meshes.
2. The modified material according to claim 1, characterized in that: The average particle size of the micron-sized calcium carbonate is 2500-3000 meshes.
3. The modified material according to claim 1, characterized in that: The silane coupling agent has a refractive index of 1.3875 at 20°C, a density of 0.985 g / ml, and a viscosity of 4.2 mm 2 / S.
4. The modified material according to claim 1, characterized in that: The auxiliary agent is composed of a chain extender, a nucleating agent, a lubricant, and an antioxidant; In terms of weight, the proportions of the components in the additive are: Chain extender: 0.2-0.4 parts by weight; Nucleating agent: 0.4-0.6 parts by weight; Lubricant: 0.3-1.2 parts by weight; Antioxidant: 0.1-0.8 parts by weight.
5. A method for preparing the modified material according to any one of claims 1 to 4, characterized in that: The steps include: Step 1, using a silane coupling agent to activate micron-sized calcium carbonate through a powder activation device to obtain activated micron-sized calcium carbonate; Step 2, adding polybutylene caproate terephthalate, activated micron-sized calcium carbonate and additives into a high-speed mixer for mixing and dispersing to obtain a dispersed material; Step 3, placing the dispersed material into a twin-screw extruder for melt extrusion to obtain an extruded material; Step 4: pelletizing and drying the extrudate to obtain the modified material.
6. The method for preparing the modified material according to claim 5, characterized in that: The powder activation device in step 1 includes a feeding system, an activation chamber, and a discharging system in sequence according to the direction of the material, and also includes a temperature control system to control the temperature of the activation chamber; The feeding sequence of the powder activation device is to first add micron-sized calcium carbonate from the feeding system into the activation chamber, and when the temperature in the activation chamber reaches 50° C., then add silane coupling agent from the feeding system into the activation chamber, and control the temperature in the activation chamber to be 120° C.; The silane coupling agent and micron-sized calcium carbonate are stirred by a stirring blade rotating at a high speed in the activation chamber, the stirring speed is 3500-5000 rad / min, and the stirring time is 10-20 min.
7. A degradation masterbatch, characterized in that: The raw materials for preparing the degradation masterbatch include the modified material according to any one of claims 1 to 4.
8. A polybutylene caproate terephthalate film, characterized in that: The polybutylene caproate terephthalate film is prepared by reacting the modified material according to any one of claims 1 to 4 or the degradation masterbatch according to claim 7 with polybutylene caproate terephthalate through a single screw film blowing machine; The mass ratio of the modified material or degradation masterbatch to polybutylene terephthalate is (5-7): (3-5); The polybutylene caproate terephthalate film has a heat sealing strength of 9-10N, a transverse elongation at break of 527-672%, a transverse tensile strength of 21.43-32.35Mpa, a longitudinal elongation at break of 501-576%, and a longitudinal tensile strength of 20.85-31.35Mpa.
9. A method for preparing the polybutylene terephthalate film according to claim 8, characterized in that: The modified material according to any one of claims 1 to 4 or the degradation masterbatch according to claim 7 is added together with polybutylene caproate terephthalate into a single screw film blowing machine, and the film is obtained by heating and melting, extruding and blowing, and cooling and solidifying.
10. The method for preparing the polybutylene terephthalate film according to claim 9, characterized in that: The single screw extruder contained in the single screw film blowing machine includes five heating temperature zones, and the temperature of each zone is set to 140-155°C for zone 1, 150-165°C for zone 2, 160-175°C for zone 3, 160-170°C for zone 4, and 150-160°C for zone 5; The blowing ratio of the single screw film blowing machine is 2-3.
Citation Information
Patent Citations
Filler composition, PBAT degradation master batch and preparation method of PBAT degradation master batch
CN116854993A
PBAT resin composite material and compound fertilizer composition
CN118978795A
Heat-resistant completely biodegradable composite material for injection molded product and formula and preparation method of heat-resistant completely biodegradable composite material
CN104788924A
Biodegradable nanometer filling function master batch and preparation method and application thereof
CN105802168A
CaCO3 surface treatment method for high-filling PBAT biodegradable film and preparation method of film
CN111423703A